On the genus Paleonura (Collembola: Neanuridae: Neanurinae) from the Americas and description of a new species from Puerto Rico - Palacios-Vargas, José G.; Soto-Adames, Felipe N. (Zootaxa, 2017)
Members of the genus Paleonura Cassagnau, 1982 from the Americas are compared with some from the holarctic region. The new species, P. borincana sp. nov., is described from Puerto Rico. It differs from other species of the genus by the combination of having cephalic setae A, B, C, D, two ocular setae and the lack of setae on the dorso-external tubercle of Abd. IV